Online Customer Reviews : Threat and Opportunity for Companies to improve products and services : An explorative case study of Text Analytics and Sentiment Analysis with Medallia in Philips - Cuomo, Alessia (My University, 2020)
The expansion of eWOM has allowed Online Customer Reviews to provide new opportunities for buyers and sellers. Consumers can benefit from millions of feedbacks online to enhance their purchase process and express their Opinion after. Companies can observe an increase in sales, and in particular, gather valuable data to improve products and services. This study, with an exploratory qualitative case study, aims to investigate the contribution that new technology can provide to companies to analyze Online Customer Reviews, thought the collection of effects with an application of the Medallia tool on Philips’s OCRs. The first results support the software adoption and validate the previous methodology proposed in the existing literature. However, some issues have been found about the autonomous mechanism and unclear outcomes. Finally, some managerial implications from this case study are proposed.
Keywords: Text Analytics, Sentiment Analysis, Opinion Mining, Online Customer Review